Propagation and Production of Gulf Bluestem - Mack Thetford; Debbie Miller (EDIS)
Gulf bluestem (Schizachyrium maritimum Chapman (Nash [Poaceae]), is considered to be the most important species of bluestem grass on the Gulf of Mexico and occurs primarily on dunes, beaches, and coastal swales (Craig 1991). Following the formation of a more seaward ridge, gulf bluestem replaces sea oats (Uniola paniculata L. [Poaceae]) on the newly protected primary ridge within 2 to17 years (Johnson 1997). This plant is a candidate for beach projects requiring planting on the back side of a primary dune, or any side of secondary dunes, or for commercial or home landscapes. This prostrate or creeping perennial spreads by long stolons and is easily distinguished by glaucous leaves, prostrate growth habit, and terminal inflorescences with stalked spikelets from 4.0 to 6.5 mm (0.15 to 0.26 in) (Clewell 1985). This document is ENH974, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date December 2004.